Thermophysical properties of newly synthesized ammonium-based protic ionic liquids: Effect of temperature, anion and alkyl chain length - Zailani, N.H.Z.O. (MDPI AG, 2020)
Ionic liquids which are often classified as low melting point salts have received significant attention from research groups and industries to be used in a wide range of applications. Many of these applications require thorough knowledge on the thermophysical properties of the ionic liquids before utilizing their full potentials in various fields. In this work, a series of alkylammonium cation and carboxylate anion-based room temperature protic ionic liquids (PILs) were synthesized by varying length of alkyl chain of the cation from diethyl to dibutyl combined with pentanoate, hexanoate and heptanoate anions. These ammonium-based PILs named as diethylammonium pentanoate DEAC5, diethylammonium hexanoate DEAC6, diethylammonium heptanoate DEAC7, dibutylammonium pentanoate DBAC5, dibutylammonium hexanoate DBAC6 and dibutylammonium heptanoate DBAC7 were characterized using Nuclear Magnetic Resonance (NMR) spectroscopy. The thermophysical properties of the PILs namely density, dynamic viscosity and refractive index were measured and analyzed. Density, Ï and dynamic viscosity, Î· were determined at T = (293.15 to 363.15) K and refractive index, nD was measured at T = (293.15 to 333.15) K. The fitting parameters are proposed for the empirical correlations of density, dynamic viscosity and refractive index. The values of thermal expansion coefficient, Î±p, molecular volume, Vm, standard entropy, Sâ¦ and lattice potential energy, Upot also have been calculated by using the specified equations. The thermal decomposition temperature, Td was also determined using a thermogravimetric analyzer (TGA) while the differential scanning calorimetry (DSC) technique provided the glass transition, Tg, melting point, Tm and crystallization, Tc temperatures of the PILs. The experimental results revealed that the dependency of the experimental values namely the Ï, Î·, nD, and Td on the alkyl chain of the anion, size of the cations and the temperature of measurement. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.